Jugovzhodna Slovenija v starejši železni dobi = South-Eastern Slovenia in the Early Iron Age Poselitev, gospodarstvo, družba = Settlement, economy, society - Dular, Janez (Opera Instituti Archaeologici Sloveniae, 2007)
The territory of present-day Slovenia reached one of its economic and cultural peaks in the 1st millennium BC, when the Hallstatt Culture prospered, its achievements being comparable with the most developed cultures in Ancient Europe. This culture arose from Urnfield Culture roots under the influence of the Mediterranean world~they adopted the new technology of iron production, implemented a new social pattern and fully developed their artistic inspiration.